Educational outcomes after serving with electronic monitoring: results from a natural experiment - Larsen, Britt Østergaard (Journal of quantitative criminology, 2017)
Objectives The paper explores the effects of electronic monitoring (EM) on young offenders’ educational outcomes and contributes to the evaluation of EM as a non-custodial sanction with a new outcome measure. Methods The study is based on a natural experiment exploiting a reform in Denmark in 2006 introducing electronic monitoring to all offenders under the age of 25 with a maximum prison sentence of 3 months. Information on program participation is used to estimate instrument variable models in order to assess the causal effects of EM on young offenders’ educational outcomes. The empirical analyses are based on a comprehensive longitudinal dataset (n = 1013) constructed from multiple official administrative registers and including a high number of covariates. Results The EM-program increases the completion rates of upper secondary education by 18 % points among program participants 3 years post-release. The EM-program includes house arrest under electronic surveillance, labor market or education participation, unannounced drug and alcohol tests and a crime preventive program. It is not possible to separate the treatment effects of the different program elements in the empirical analyses.